High performance work system-performance nexus in Nigerian SMEs: a moderated mediation study - Ismail, Abdussalaam Iyanda (2018)
Existing empirical evidence identifies research issues on the dwindling performance of Nigerian SMEs, the existence of vague processes (black box) between organizational inputs (high performance work system [HPWS]) and organizational output (organizational performance), inconsistent HPWS configuration, and the contingency theory's supposition that the context within which organizations operate matters most. In addressing these issues, this moderated mediation study, which was underpinned by the contingency theory and RBV, investigated the effect of HPWS on Nigerian SMEs' performance with the integration of the mediating role of employee creativity and the moderating role of management philosophy in the HPWS-SME performance nexus. Using the cross-sectional research approach, data were collected from a sample of 518 SME managers in Nigeria. The Partial Least Squares Method (PLS) algorithm and the bootstrapping technique were used to test the study's hypotheses. The results provided support for nine out of the twelve hypotheses. The overall findings signified a positive effect of HPWS on SME financial and non-financial performance. The results also indicated that HPWS positively influenced performance through employee creativity, and management philosophy was found to interact with employee creativity in enhancing performance. Going by these results, it can be asserted that this moderated mediation research has widened the scope of the extant business theories and facilitated response to the "when", "how" and "why" questions on the relationship between HPWS and organizational performance. Also, HPWS in the Nigerian SMEs is not enough to stimulate high performance until it induces employee creativity, and organizational performance hinges on the effective alignment of managerial attitudes and philosophies with HPWS. Thus, SME managers and other stakeholders need to entrench HPWS that is employee-oriented. Lastly, the implications, limitations and suggestions for future research were discussed.